2013
DOI: 10.1111/gcb.12216
|View full text |Cite
|
Sign up to set email alerts
|

Initial nitrous oxide, carbon dioxide, and methane costs of converting conservation reserve program grassland to row crops under no‐till vs. conventional tillage

Abstract: Around 4.4 million ha of land in USDA Conservation Reserve Program (CRP) contracts will expire between 2013 and 2018 and some will likely return to crop production. No-till (NT) management offers the potential to reduce the global warming costs of CO2, CH4, and N2O emissions during CRP conversion, but to date there have been no CRP conversion tillage comparisons. In 2009, we converted portions of three 9–21 ha CRP fields in Michigan to conventional tillage (CT) or NT soybean production and reserved a fourth fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 50 publications
6
59
0
Order By: Relevance
“…We found that the highest CH 4 uptake occurred in CL that had been cropped for more than 30 years, which was inconsistent with the findings of Mosier and Delgado (1997) who found that soil CH 4 oxidation in the shortgrass steppe had not recovered even after plowing for 79 years. Ruan and Robertson (2013) observed no significant difference in CH 4 uptake between a Conservation Reservation Program (CRP) pasture (Bromus inermis) and a converted soybean (Glycine max) cropland in the Great Plains of Northern America. Ussiri et al (2009) reported higher CH 4 uptake in no-till fields compared to conventionally tilled fields.…”
Section: Discussionmentioning
confidence: 90%
“…We found that the highest CH 4 uptake occurred in CL that had been cropped for more than 30 years, which was inconsistent with the findings of Mosier and Delgado (1997) who found that soil CH 4 oxidation in the shortgrass steppe had not recovered even after plowing for 79 years. Ruan and Robertson (2013) observed no significant difference in CH 4 uptake between a Conservation Reservation Program (CRP) pasture (Bromus inermis) and a converted soybean (Glycine max) cropland in the Great Plains of Northern America. Ussiri et al (2009) reported higher CH 4 uptake in no-till fields compared to conventionally tilled fields.…”
Section: Discussionmentioning
confidence: 90%
“…Various studies have shown that both net GWP and GHGI were lower with no-tillage than conventional tillage, regardless of soil and climatic conditions, cropping systems, and methods Agricultural Management Impact on Greenhouse Gas Emissions http://dx.doi.org/10.5772/intechopen.72368 91 of calculations [3,7,44,47,49,55]; Sainju [56] observed that reductions in net GWP and GHGI due to no-tillage vs. conventional tillage vary among regions with various soil and climatic conditions, but largest difference occurred in sandy soil under moderate annual precipitation (900 mm). Net GWP values, however, increased in regions with higher air temperature.…”
Section: Tillagementioning
confidence: 99%
“…Some have used the sum of CO 2 equivalents of N 2 O and CH 4 emissions [21,41,42], while others [43,44] have included CO 2 equivalents of all three GHGs. Still others have used CO 2 equivalents of N 2 O and CH 4 emissions and soil carbon sequestration rate [45][46][47].…”
Section: −1mentioning
confidence: 99%
See 1 more Smart Citation
“…Total available N including ammonium (NH þ 4 ) and nitrate (NO À 3 ) availability was estimated using in situ ion exchange resin strips to minimize sampling disturbance (Ruan and Robertson 2013). Three pairs of anion and cation resin strips (2.5 cm 9 10 cm 9 0.62 mm thick; GE Power & Water, Trevose, PA, USA) were buried directly to a soil depth of 12 cm in each treatment plot one day before the experiment commenced each winter and left in place for the season.…”
Section: Soil Inorganic Nitrogenmentioning
confidence: 99%